2017
DOI: 10.1017/aae.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Beef Cattle Retained Ownership and Profitability in Tennessee

Abstract: Abstract. The effect of animal characteristics and placement decisions on retained ownership profitability of Tennessee cattle from 2005 to 2015 was determined using a mixed model regression. Ex post simulation analysis examined retained ownership profitability by placement season under different animal characteristic and corn price scenarios. Regression results indicate that placement weight, placement season, days on feed, animal health, and animal sex affect retained ownership profitability. Simulation resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…It is important to note the economics of grazing stocker cattle on WSGs, or any retained ownership decision, is dependent on several factors, such as feed costs and cattle prices. Historically, cattle prices per unit decrease as stocker cattle weights increases; however, this decrease can be affected by feed costs (Tang et al., ). Higher feed costs can increase cattle prices for heavier animals, thus increasing the demand for extending grazing days to increase the weight of feeder cattle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note the economics of grazing stocker cattle on WSGs, or any retained ownership decision, is dependent on several factors, such as feed costs and cattle prices. Historically, cattle prices per unit decrease as stocker cattle weights increases; however, this decrease can be affected by feed costs (Tang et al., ). Higher feed costs can increase cattle prices for heavier animals, thus increasing the demand for extending grazing days to increase the weight of feeder cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Retaining stocker cattle to graze incurs risk due to variability in prices and beef gains (Tang, Lewis, Lambert, Griffith, & Boyer, 2017). Risk can be incorporated in this analysis by consider the expected net returns as well as the variability of those net returns.…”
Section: Simulation and Risk Analysismentioning
confidence: 99%
“…The important distinction here is that feeder cattle are not ready for harvest, but rather are an input into the cattle finishing industry. For that reason, the value of feeder cattle is typically evaluated from a derived demand perspective, meaning that feeder cattle values are driven by factors that impact the profitability of their placement into these finishing programs (Bulut and Lawrence, 2007;Burdine et al, 2014;Halich and Burdine, 2015;Schulz, Dhuyvetter, and Doran, 2015;Lewis et al, 2016;Mallory et al, 2016;Tang et al, 2017;Williams et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last couple of decades, a great deal has been learned about how factors such as cattle characteristics, changes in corn price, and lot size impact feeder cattle values. Studies have shown that gender, breed, hide color, marketing attributes related to health programs, and how the cattle have been raised all impact prices (Bulut and Lawrence, 2007;Burdine et al, 2014;Halich and Burdine, 2015;Lewis et al, 2016;Mallory et al, 2016;Schulz, Dhuyvetter, and Doran, 2015;Tang et al, 2017;Williams et al, 2012). For example, black-hided cattle have tended to be associated with higher prices (Bulut and Lawrence, 2007;Burdine et al, 2014;Zimmerman et al, 2012;Mallory et al, 2016;Parish et al, 2018;Williams et al, 2012) and Dhuyvetter and Schroeder (2000) found that continental cattle sold at a discount to English cattle.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, Lopes e Magalhães (2005) destacam que para o êxito da atividade exigem-se conhecimentos em administração financeira, nutrição animal, manejo nutricional, produção de volumosos, aquisição de insumos e de animais de reposição. Adicionalmente, a pressão cada vez maior para intensificação dos sistemas de produção de alimentos, aliado aos custos de insumos cada vez maiores, torna-se essencial fazer análises de índices econômicos para monitoramentos dos sistemas de produção e tomada de decisões que garantem o sucesso da atividade (Sartorello et al, 2018;Tang et al, 2017).…”
unclassified